Combination of Polygoni Multiflori Radix Praeparata and Acori Tatarinowii Rhizoma Alleviates Learning and Memory Impairment in Scopolamine-Treated Mice by Regulating Synaptic-Related Proteins - Funan Ning; Funan Ning; Lvyi Chen; Linlin Chen; Xin Liu; Yao Zhu; Jiayi Hu; Guangjing Xie; Jiaxuan Xia; Kun Shi; Zhou Lan; Ping Wang (Frontiers in Pharmacology, 2021)
Polygoni Multiflori Radix Praeparata (ZhiHeShouWu, PMRP) and Acori Tatarinowii Rhizoma (ShiChangPu, ATR) and their traditional combination (PA) are frequently used in traditional Chinese medicine to prevent and treat Alzheimer disease (AD) based on the theory that PMRP tonifies the kidney and ATR dissipates phlegm. However, the components of PA and their mechanisms of action are not known. The present study analyzed the active components of PA, and investigated the protective effect of PA against cognitive impairment induced by scopolamine in mice along with the underlying mechanism.The aqueous extract of PA was analyzed by high-performance liquid chromatography–mass spectrometry (HPLC-MS) and gas chromatography (GC)-MS in order to identify the major components. To evaluate the protective effect of PA against cognitive dysfunction, mice were orally administered PA, PMRP, or ATR for 30 days before treatment with scopolamine. Learning and memory were assessed in mice with the Morris water maze test; neurotransmitter levels in the hippocampus were analyzed by HPLC-MS; and the expression of synapse-related proteins in the hippocampus was detected by western blotting and immunohistochemistry. Eight active compounds in PA and rat plasma were identified by HPLC-MS and GC-MS. Plasma concentrations of 2,3,5,4′-tetrahydroxystilbene-2-O-β-d-glucoside, emodin, α-asarone, and asarylaldehyde were increased following PA administration; meanwhile, gallic acid, emodin-8-O-β-d-glucopyranoside, β-asarone, and cis-methyl isoeugenol concentrations were similar in rats treated with PA, PMRP, and ATR. In scopolamine-treated mice, PA increased the concentrations of neurotransmitters in the hippocampus, activated the brain-derived neurotrophic factor (BDNF)/extracellular signal-regulated kinase (ERK)/cAMP response element binding protein (CREB) signaling pathway, and increased the expression of p90 ribosomal S6 kinase (p90RSK) and postsynaptic density (PSD)95 proteins. Thus, PA alleviates cognitive deficits by enhancing synaptic-related proteins, suggesting that it has therapeutic potential for the treatment of aging-related diseases such as AD.